2014
DOI: 10.1016/j.athoracsur.2013.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Fluorodeoxyglucose-Positron Emission Tomography Within the Clinical Practice of the American College of Surgeons Oncology Group Z4031 Trial to Diagnose Clinical Stage I Non-Small Cell Lung Cancer

Abstract: Background Fluoro-deoxyglucose positron emission tomography (FDG-PET) is recommended for diagnosis and staging of NSCLC. Meta-analyses of FDG-PET diagnostic accuracy demonstrated sensitivity and specificity of 96% and 78%, respectively but were performed in select centers introducing potential bias. This study evaluates the accuracy of FDG-PET to diagnose NSCLC and examines differences across enrolling sites in the national ACOSOG Z4031 trial. Methods 959 eligible patients with clinical stage I (cT1-2N0M0) k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 14 publications
0
55
0
Order By: Relevance
“…6) The secondary analysis of American College of Surgeons Oncology Group (ACOSOG) Z4031 trial showed the result of diagnostic accuracy of PNs. 20) Unfortunately, the study did not require a standard PET/CT protocol and an SUV cut-off value of 2.5 was the one of the diagnostic indications. These papers suggested that the use of a cut-off point for FDG accumulation or for SUV is controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6) The secondary analysis of American College of Surgeons Oncology Group (ACOSOG) Z4031 trial showed the result of diagnostic accuracy of PNs. 20) Unfortunately, the study did not require a standard PET/CT protocol and an SUV cut-off value of 2.5 was the one of the diagnostic indications. These papers suggested that the use of a cut-off point for FDG accumulation or for SUV is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…9) Grogan, et al revealed that PET accuracy improved with increasing sizes of lesions, from 67% for 1-2-cm lesions (sensitivity, 76%; specificity, 35%) to 84% for 3-5-cm lesions (sensitivity, 90%; specificity, 18%; P <0.001). 20) Our study included 30 patients with nodules ≤1 cm. Among them, 12 patients had malignant nodules with SUV indices ≥1.2; that is, there were no patients with false-positive results.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moreover, PET/CT after SABR for lung malignancies may be utilized as a surrogate of tumour response, according to available literature data. [24][25][26] On-board CBCT has been recently implemented in clinical practice for precise treatments. Another potential application of CBCT could be the ability to assess tumour volume changes during RT.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumor histologies are attained in all surgical cases, whereas the diagnoses rely on positron emission tomography/CT morphological criteria in a significant number of RT patients. The sensitivity of positron emission tomography/CT ranges between 68 and 100%, but it only has a moderate positive predictive value [9]. …”
Section: Discussionmentioning
confidence: 99%